Examining readers' reactions to difficult narratives: a psycho-stylistic approach to Virginia Woolf's use of free indirect style - Grisot, Giulia (2020)
This thesis aims to explore the processes that readers engage in when they encounter difficulties in literary texts and to add scientific value to existing theoretical assumptions about difficult literature, combining stylistic analyses with psycholinguistic research methods.